Knowledge, Attitudes, and Practices of Dog Owners Regarding Dog-Related Diseases in Mvomero and Morogoro Districts, Tanzania - Amina Ramadhani Issae; Hezron Emanuel Nonga (Journal of Epidemiology and Public Health, 2025)
Background: Dogs were the earliest animals domesticated by humans for various purposes, but receive little attention from the community and may be sources of diseases in humans and other animals. In Tanzania, most dogs are Mongrels and are primarily found in rural areas where they receive limited veterinary care. Therefore, the study aimed to assess the knowledge, attitudes, and practices of dog keepers regarding dog management, and their awareness of zoonoses, to develop effective disease prevention and control programs.Subjects and Method: A cross-sectional study was conducted between October 2017 and January 2018 in the Mvomero and Morogoro districts of Tanzania. The study used a simple random sampling method, whereas a structured questionnaire was administered to 200 dog keepers. Statistical Package for Social Sciences (SPSS) version 20 was used for data analysis. The independent variables were demographic characteristics of dog keepers (age, gender, education, and location), while dependent variables included knowledge of dog management, attitudes toward dogs, and practices.Results: The study found that 59% of respondents had fair to good knowledge of dog management, though practices were generally poor, with most dog keepers owning dogs for security purposes. While 87% were aware of zoonotic diseases, particularly rabies, vaccination rates were higher in Morogoro than in Mvomero (p<0.05). Negative experiences with dogs were reported by 78% of respondents, and attitudes towards dogs were more negative in Mvomero than in Morogoro (p=0.007).Conclusion: The study concludes that dogs in Morogoro are poorly managed, live-in unhygienic conditions, rarely receive veterinary services, and experiences suffering of different kinds, which is contrary to animal welfare principles. Therefore, integrative approaches to raising public awareness about dog management practices in the study areas and other regions of Tanzania are recommended to safeguard the health of both dogs and humans.